2021
DOI: 10.1002/14651858.cd012851.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for promoting the eruption of palatally displaced permanent canine teeth, without the need for surgical exposure, in children aged 9 to 14 years

Abstract: Interventions for promoting the eruption of palatally displaced permanent canine teeth, without the need for surgical exposure, in children aged 9 to 14 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 72 publications
1
3
0
6
Order By: Relevance
“…There are many authors who have researched the efficacy of primary canine extraction as a treatment of choice for successful eruption of PDC in young individuals ( 29 - 33 ). Even though chronological age, suggested for this prevention procedure, coincides with the results of skeletal maturation delay in this research, Benson et al found no certain evidence that this procedure will help the eruption of PDC without surgical approach ( 34 ).…”
Section: Discussionsupporting
confidence: 48%
“…There are many authors who have researched the efficacy of primary canine extraction as a treatment of choice for successful eruption of PDC in young individuals ( 29 - 33 ). Even though chronological age, suggested for this prevention procedure, coincides with the results of skeletal maturation delay in this research, Benson et al found no certain evidence that this procedure will help the eruption of PDC without surgical approach ( 34 ).…”
Section: Discussionsupporting
confidence: 48%
“…Un diente impactado es aquel que no realiza su proceso de erupción a la arcada dentaria en el tiempo deseado, permaneciendo en el hueso alveolar, considerando que el diente emerge cuando sus dos tercios de raíz se han formado (Andrade et al, 2019), este proceso puede verse comprometido por una interferencia en el trayecto de erupción; se puede identificar mediante un análisis clínico como es la palpación, en la que a la edad entre 10 a 11 años el canino es palpable a nivel del surco bucal, además es necesaria una evaluación radiográfica para confirmar o descartar una impactación del canino (Lövgren et al, 2019;Elangovan et al, 2019;Benson et al, 2021)involving surgery to uncover the tooth and prolonged orthodontic (brace. Lövgren et al en el año 2020, menciona que los pacientes que presentaron impactación del canino maxilar tenían un desarrollo dental retrasado (Lövgren et al, 2021).…”
Section: Impactación Del Canino Maxilarunclassified
“…Harada-karishima et al consideran que los caninos impactados palatinamente responden a un componente genético y en una posición labial se asocian con una inadecuada longitud del arco (Harada-Karashima et al, 2021). Benson refiere que existen estudios en los cuales se establece que mientras más cerca se encuentran los caninos impactados de la línea media, tienen menos probabilidad de irrumpir en la cavidad bucal (Benson et al, 2021).…”
Section: Impactación Del Canino Maxilarunclassified
See 2 more Smart Citations